2022
DOI: 10.1111/bjop.12553
|View full text |Cite
|
Sign up to set email alerts
|

Metacognition during unfamiliar face matching

Abstract: Kruger and Dunning (1999) described a metacognitive bias in which insight into performance is linked to competence: poorer performers are less aware of their mistakes than better performers. Competence-based insight has been argued to apply generally across task domains, including a recent report investigating social cognition using a variety of face-matching tasks. Problematically, serious statistical and methodological criticisms have been directed against the traditional method of analysis used by researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 67 publications
0
16
1
Order By: Relevance
“…Recent work on the general population compared these two types of estimates. They showed that global assessments of ability may not be as informative as decision-based metrics, such as confidence on a trial (Kramer et al, 2022). It would be useful for face specialist recruitment to directly compare the utility of self-reported estimates of ability from questionnaires and implicit, decision-based estimates of accuracy, such as those obtained in the current study.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Recent work on the general population compared these two types of estimates. They showed that global assessments of ability may not be as informative as decision-based metrics, such as confidence on a trial (Kramer et al, 2022). It would be useful for face specialist recruitment to directly compare the utility of self-reported estimates of ability from questionnaires and implicit, decision-based estimates of accuracy, such as those obtained in the current study.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, this moderate degree of metacognitive awareness is observed for both self-assessed measures from previous studies and the implicit, decision-based measures from this study (average confidence and difficulty ratings). Recent work on the general population compared global and decision-based estimates of accuracy directly (Kramer et al, 2022). They showed that global assessments of ability may not be as informative as decision-based metrics, such as confidence on a trial.…”
Section: Behavioral Insight: Confidence Difficulty and Accuracymentioning
confidence: 99%
“…Of course, not all participants are equally capable of differentiating between their correct and incorrect responses with regard to confidence. Across two different tasks, Kramer et al (2022) found that increased competence with face matching ( i.e ., a higher overall score on objective tests) predicted greater metacognitive insight, represented by a larger distinction between correct and incorrect responses in terms of confidence ratings given. The best performers were significantly more confident in their correct ( vs incorrect) responses, while the worst performers’ confidence ratings failed to distinguish between correct and incorrect decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supporting this account would be provided by an interaction between objective and self-assessed abilities when considering metacognitive sensitivity. As such, a measure of self-assessed ability is needed—something which was absent in Kramer et al (2022) .…”
Section: Introductionmentioning
confidence: 99%
“…The DK effect also occurs in different environments, for example the problem of face recognition. This situation was recently investigated by Kramer et al (2022), who found imperfect correlation between self-insight and competence.…”
Section: Introductionmentioning
confidence: 99%